2017
DOI: 10.1371/journal.pone.0184470
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the endogenous omega-3 fatty acid and oxylipin profile in vivo—A comparison of the fat-1 transgenic mouse with C57BL/6 wildtype mice on an omega-3 fatty acid enriched diet

Abstract: Dietary intervention and genetic fat-1 mice are two models for the investigation of effects associated with omega-3 polyunsaturated fatty acids (n3-PUFA). In order to assess their power to modulate the fatty acid and oxylipin pattern, we thoroughly compared fat-1 and wild-type C57BL/6 mice on a sunflower oil diet with wild-type mice on the same diet enriched with 1% EPA and 1% DHA for 0, 7, 14, 30 and 45 days. Feeding led after 14–30 days to a high steady state of n3-PUFA in all tissues at the expense of n6-PU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 64 publications
12
22
0
Order By: Relevance
“…Interestingly, serum has similarly high levels of ARA oxylipins, but very low levels of DHA oxylipins (Leng et al, , ). The rat whole brain oxylipin profile reported herein was similar to the female mouse whole brain profile (Ostermann et al, ). In all tissues, including the brain, the oxylipin levels do not necessarily reflect precursor PUFA levels, demonstrating that PUFA levels cannot be used to predict oxylipin levels and need to be measured directly.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, serum has similarly high levels of ARA oxylipins, but very low levels of DHA oxylipins (Leng et al, , ). The rat whole brain oxylipin profile reported herein was similar to the female mouse whole brain profile (Ostermann et al, ). In all tissues, including the brain, the oxylipin levels do not necessarily reflect precursor PUFA levels, demonstrating that PUFA levels cannot be used to predict oxylipin levels and need to be measured directly.…”
Section: Discussionsupporting
confidence: 81%
“…Fifth, different solid phase extraction methods vary in their efficacy of oxylipin extraction; however, the method used in this study is the most efficient in general, although some of the ARA-derived CYP oxylipins may not be extracted as well as by other procedures Puppolo et al, 2014). This may explain why fewer of these metabolites were observed in the whole rat brain herein, compared to whole mouse brain (Ostermann et al, 2017b). Finally, the levels of PUFA in the control, LNA, and LNA + ALA diets are within the ranges found in human diets, but the n-3 PUFA added to the ALA, EPA, and DHA levels would be more difficult to attain without supplementation.…”
Section: Discussionmentioning
confidence: 95%
“…In conclusion, while it has previously been shown that the oxylipin content of the brain can be modified by changes in the composition of a chronically consumed diet [12][13][14][15][16][17], in this study we demonstrate that a single meal exposure is sufficient to produce differences in oxylipin content. We also demonstrate that fasting alters brain oxylipin content.…”
Section: Discussionsupporting
confidence: 51%
“…In previous work conducted in our laboratory, we found that the consumption of a Western diet over the period of three months increased arachidonic acid derived oxylipins and altered the fatty acid profiles of the brains of mice [12]. Further, others have shown that various modifications of a chronically consumed diet have the potential to modify brain oxylipin levels [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 73%
“…15 For example, in mice and rats dietary EPA and DHA induced a shift in the overall tissue oxylipin profile by decreasing ARA derived oxylipins and increasing n3-PUFA derived oxylipins. 16,17 Several oxylipins synthesized from EPA or DHA exert less inflammatory activity compared to those from ARA, e.g. EPA derived LTB 5 vs. ARA derived LTB 4 18 or are directly involved in the resolution of inflammation, e.g.…”
Section: Introductionmentioning
confidence: 99%